Prevalência de disfagia orofaríngea no acidente vascular cerebral após cirurgia cardíaca - Almeida, Tatiana Magalhães De; Cola, Paula Cristina; Magnoni, Daniel; França, João Ítalo Dias; Silva, Roberta Gonçalves Da (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
Abstract:PURPOSE: to determine the prevalence of oropharyngeal dysphagia in patients undergoing cardiac surgery and who developed stroke in a public referral hospital.METHODS: a retrospective descriptive clinical cross-sectional study conducted by collecting data on clinical assessment protocols of oropharyngeal swallowing in the period November 2010 to November 2011, including the protocols of 25 individuals for clinical evaluation of oropharyngeal dysphagia with post-operative stroke during the study period who were assisted by the Speech-Language Pathology team. Clinical swallowing assessment was based on clinical tools and swallowing classified as normal, mild, moderate and severe dysphagia.RESULTS: of the twenty-five (100%) patients, 24 (96%) presented dysphagia in clinical evaluation and 1 (4%) did not (95% [IC]: 79.6- 99.9). It was found that 41.66% had severe dysphagia, 33.66% moderate and 25% mild dysphagia.CONCLUSION: there was a high prevalence of oropharyngeal dysphagia in patients with stroke after cardiac surgery.

Resumo:OBJETIVO: determinar a prevalência de disfagia orofaríngea em indivíduos submetidos à cirurgia cardíaca e que evoluíram com Acidente Vascular Cerebral em Hospital Público de Referência.MÉTODOS: estudo clínico descritivo, retrospectivo, realizado por meio da coleta de dados de protocolos de avaliação clínica da deglutição orofaríngea, no período de novembro de 2010 á novembro de 2011. Foram incluídos os 25 protocolos de avaliação clínica para disfagia orofaríngea de indivíduos que fizeram cirurgia cardíaca e evoluíram com Acidente Vascular Cerebral no pós-operatório, durante o período estudado, e que foram assistidos pela equipe de Fonoaudiologia. A avaliação clinica da deglutição foi baseada em instrumento clinico e a deglutição classificada como normal, disfagia leve, moderada e grave.RESULTADOS: dos 25 (100%) indivíduos, 24 (96%) apresentaram algum grau de disfagia orofaríngea na avaliação clínica. (95% [IC]: 79,6- 99,9). Constatou-se que 41,66% apresentaram disfagia grave, 33,66% disfagia moderada e 25% disfagia leve.CONCLUSÃO: é alta a prevalência de disfagia orofaríngea em indivíduos com Acidente Vascular Cerebral após cirurgia cardíaca.
Prevalence of oropharyngeal dysphagia in stroke after cardiac surgery
Keywords: Deglutition Disorders; Stroke; Thoracic Surgery; Transtornos de Deglutição; Acidente Vascular Cerebral; Cirurgia Torácica